Towards CMOS integrated microsystems for single cell transfection and analysis - Punjiya, Meera. (Tufts University. Tisch Library., 2019)
Nearly 3 decades ago cellular biologists established that signiﬁcant and functionally relevant cellular heterogeneity exists within isogenic cell populations. This cellular heterogeneity has led to growing interest in the development of instrumentation capable of single-cell analysis. Such instrumentation would be capable of decoupling single cells from a larger population, selectively altering their microenvironment and subsequently analyzing them, either chemically or optically, in a controllable manner. While many methods have been developed, these techniques have yet to provide for time-resolved single-cell measurements in a high-throughput format. In hope of bridging this gap, a multitude of microﬂuidic and lab-on-chip (LoC) technologies for cell analyses have emerged. These technologies provide unmatched parallelism with multiple complex functions integrated into a single platform, oﬀering true potential for time-resolved single-cell analysis. Immobilization techniques, chemical and electrical transfection techniques and subsequent analytical methods have independently been developed as LoC technologies, but are reliant on external electronics, a key component for measurement. More recently, a new class of LoC systems have emerged which exploit the well developed complementary metal-oxide-semiconductor (CMOS) fabrication technologies of silicon microelectronics. These lab-on-CMOS (LoCMOS) platforms are fully integrated and self-contained, implementing hybrid sensing, data processing and communication capabilities on a single platform. This thesis explores microfabricated LoC and LoCMOS platforms for single-cell analysis towards the goal of a completely integrated platform capable of single-cell isolation, controllable electroporation, lysis and functional imaging. We contribute the design of two all-electronic platforms, each with a unique advantage. We begin with a microfabricated platform for simultaneous dielectrophoretic trapping and transfection and build to a complete CMOS system-on-chip with all of the required functions for single-cell analysis. We demonstrate functionality through manipulation and plasmid transfection of human embryonic kidney cells. Lastly, we attempt to add additional functionality to this platform through inclusion of an optical analysis modality. Here the design and implementation of a novel CMOS architecture for ﬂuorescent lifetime imaging microscopy is presented and evaluated.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Valencia Koomson, Brian Timko, and Lalitha Parameswaran.; Keyword: Electrical engineering.